Foreign body in the bronchus in children: 22 years experience in a tertiary care paediatric centre - Shasanka Shekhar Panda; Minu Bajpai; Amit Singh; Dalim Kumar Baidya; Manisha Jana (Wolters Kluwer Medknow Publications, 2014)
Background: Our objective was to assess types, presentation, duration of symptoms and usefulness of rigid bronchoscopy for diagnosis and treatment of bronchial foreign body (FB) in children. Materials and Methods: Records of children with documented FB aspiration treated in Department of Paediatric Surgery from January 1991 to December 2012 were analysed retrospectively. Diagnosis was made on the basis of history, clinical examination, radiological evaluation and bronchoscopy. Results: A total of 196 children underwent emergency rigid bronchoscopy for suspected bronchial FB and in 173 cases FB was found. Out of 173 cases, 118 (68.21%) were males and 55 (31.79%) were females. Mean age was 3.7 years (range: 2 months-12 years) while mean duration of symptoms was 28 h (range: from 3 h to 4 months). Most common FB bronchus found was peanut 141 (81.50%). FB was localised to right bronchus in 112 (64.74%) cases while in 44 (25.43%) cases left bronchus was involved. In 17 (9.83%) cases FB was seen at carina only. Cough was the most common presenting symptom in 131 (75.72%) cases. The most common finding in chest X-ray was consolidation-collapse lung or emphysematous lung in 83 (47.97%) cases followed by the flattening of the diaphragm in 17 (9.83%) cases. In 35 (20.23%) cases chest X-ray was found to be normal. Pre-operative endotracheal intubation was done in 13 (7.51%) cases while 20 (11.56%) cases required post-operative mechanical ventilation. Conclusion: High index of suspicion should be kept for bronchial FB in children who present with suggestive history of FB ingestion even with normal physical and radiological evaluation.